PERANAN ADMINISTRASI GURU DALAM MELENGKAPI PENILAIAN KINERJA GURU DI SDN 1 GALAGAMBA KEC. CIWARINGIN, KABUPATEN CIREBON- JAWA BARAT - Nani Nuraini Sarah; Desilia Purnama Dewi; Ratna Suminar (Universiitas Pamulang, 2022)
ABSTRACT Teachers are expert teachers who have important tasks in the form of guiding, fostering, assessing, educating, training, teaching, directing and evaluating students at the formal level of elementary to high school education. Thus teacher performance assessments must be held so that every teacher can develop in a better direction. In order for the implementation of PKG to run smoothly, there are efforts or factors that need to be observed, including the readiness of teachers, assessment instruments, assessors, school principals. The scope of the Teacher Performance Assessment on the limits of the teacher's task load and responsibilities include: Designing lessons, conducting lessons, assessing learning outcomes, guiding & training students, as well as carrying out additional tasks in the main activities according to the teacher's workload. Community Service (PKM) is one of the elements of the Tri Dharma of Higher Education which cannot be separated from its implementation with the other two (2) dharmas. In its implementation, it must be able to involve other academics, such as: lecturers, education staff, students and alumni. This Community Service Report (PKM) is planned to be published in the secretarial PKM journal, with the aim that the academic community and other readers can benefit from it. Keywords: Administration, Teacher, Performance Appraisal ABSTRAK Guru merupakan pengajar ahli yang memiliki tugas penting berupa membimbing, membina, menilai, mendidik, melatih, mengajar, mengarahkan dan mengevaluasi siswa pada jenjang formal pendidikan dasar hingga menengah atas. Dengan demikian penilaian kinerja guru harus diadakan agar setiap guru bisa berkembang ke arah yang lebih baik. Agar penerapan PKG dapat berlangsung dengan lancar, terdapat usaha atau faktor yang perlu dicermati, diantaranya adalah kesiapan dari guru, instrumen penilaian, penilai, kepala sekolah. Ruang lingkup Penilaian Kinerja Guru pada batasan beban tugas dan tanggung jawab guru diantaranya adalah: Merancang pembelajaran, melakukan pembelajaran, menilai hasil pembelajaran, membimbing & melatih siswa, serta melakukan tugas tambahan yang ada pada kegiatan utama sesuai dengan beban kerja guru. Pengabdian Kepada Masyarakat (PKM) merupakan salah satu unsur Tri Dharma Perguruan Tinggi yang tidak dapat dipisahkan pelaksanaannya dengan dua (2) dharma lainnya. Dalam pelaksanaannya harus dapat melibatkan civitas akademika lainnya, seperti: dosen, tenaga kependidikan, mahasiswa serta alumni. Laporan Pengabdian Kepada Masyarakat (PKM) ini direncanakan terbit dalam jurnal PKM sekretari, dengan tujuan agar dapat diambil manfaatnya oleh civitas akademika serta pembaca lainnya. Kata Kunci : Administrasi, Guru, Penilaian Kinerja